Relationship between Creep Property and Loading-Rate Dependence of Strength of Artificial Methane-Hydrate-Bearing Toyoura Sand under Triaxial Compression - Kuniyuki Miyazaki; Norio Tenma; Tsutomu Yamaguchi (Energies, 2017)
Methane hydrate is anticipated to be a promising energy resource. It is essential to consider the mechanical properties of a methane hydrate reservoir to ensure sustainable production, since its mechanical behavior may affect the integrity of the production well, the occurrence of geohazards, and gas productivity. In particular, the creep property of methane-hydrate-bearing sediment is thought to have great significance in the long-term prediction of the mechanical behaviors of a reservoir. In earlier studies, triaxial compression tests were conducted on artificial methane-hydrate-bearing Toyoura sand under three axial-loading conditions, i.e., constant-strain-rate test, constant-stress-rate test, and creep (constant-stress) test. In this paper, the time-dependent properties of the methane-hydrate-bearing Toyoura sand observed in these tests were quantitatively discussed and found to be almost in agreement. The creep life obtained from the creep tests had a reasonably strong correlation with the loading-rate dependencies of strength, obtained from the constant-strain-rate tests and constant-stress-rate tests based on a simple hypothesis. The findings are expected to be used to develop a constitutive model considering the time-dependent behaviors of hydrate-bearing soil in future studies, and to improve the reliability of long-term prediction of the geomechanical response to gas extraction from a reservoir.